Kebijakan Ekonomi Politik Stated-Centered dan Rent-Seeking Behavior dalam Kebijakan Pangan Impor Beras - Wahyu Riawanti (Magister Ilmu Administrasi Publik, 2011)
This present a critical assessment of the political economy that underlie food policy and rice import in Indonesia. State-centric behavior and rent-seeking practices are important determinants of food policy formulation in Indonesia. The study analyzes the importation of rice by the Indonesian government. Study result show that rice policy is based on three main point which are: relationship between farmer's term of trade (NTP), ruse production and distribution; and political power in policy formulation.